Prognozowanie w przedsiębiorstwie - Dittmann, Paweł (Business Forecasting, 2006)
The paper shows the problems of forecasting in an enterprise. It identifies possibilities of using forecasts and presents methods of evaluation the quality of forecasts and criteria for choosing forecasting methods. There has been also described the problem of the integration of forecasting methods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1140, s. 9-22